2010
DOI: 10.1002/jso.21539
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor‐1α gene polymorphism G1790A and its interaction with tobacco and alcohol consumptions increase susceptibility to hepatocellular carcinoma

Abstract: Genetic polymorphism at G1790A of HIF-1alpha is an important factor for determining the susceptibility to hepatocellular carcinoma. The interaction effects of G1790A heterozygotes to tobacco and to alcohol consumption significantly increase the risk to develop hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 43 publications
3
34
1
1
Order By: Relevance
“…Thus, no significant association of g.G1790A polymorphism was observed in the present study similar to previous reports for breast cancer (Apaydin et al, 2008;Kim et al, 2008;Naidu et al, 2009). Increased frequency of A allele has been reported in renal (Ollerenshaw et al, 2004), gastric (Li et al, 2009), oral (Munnoz-Guerra et al, 2009, hepatocellular (Hsiao et al, 2010) and pancreatic cancer . In pancreatic cancer, g.G1790A has been associated with greater amount of tumor-produced HIF-1α and bigger tumor volumes indicating its role in carcinogenesis and cancer progression .…”
Section: Discussionsupporting
confidence: 89%
“…Thus, no significant association of g.G1790A polymorphism was observed in the present study similar to previous reports for breast cancer (Apaydin et al, 2008;Kim et al, 2008;Naidu et al, 2009). Increased frequency of A allele has been reported in renal (Ollerenshaw et al, 2004), gastric (Li et al, 2009), oral (Munnoz-Guerra et al, 2009, hepatocellular (Hsiao et al, 2010) and pancreatic cancer . In pancreatic cancer, g.G1790A has been associated with greater amount of tumor-produced HIF-1α and bigger tumor volumes indicating its role in carcinogenesis and cancer progression .…”
Section: Discussionsupporting
confidence: 89%
“…Two common functional polymorphisms, C1772T (rs11549465 C>T) and G1790A (rs11549467 G>A), in the human HIF-1α gene that cause amino acid substitutions within the oxygen-dependent degradation domain may result in the overexpression of this protein and subsequent changes in the expression of downstream target genes, thus contributing to cancer development and progression (Chau et al, 2005). Several previous studies have suggested that HIF-1α C1772T and G1790A polymorphisms may play important roles in the risk of digestive cancer (Ling et al, 2005;Fransen et al, 2006;Li et al, 2009;Hsiao et al, 2010;Kang et al, 2011;Wang et al, 2011), while other studies found no convincing evidence of these polymorphisms in increasing susceptibility to digestive cancer (Kuwai et al, 2004;Knechtel et al, 2010). This controversy could be explained with several reasons such as the differences in study designs, sample size, ethnicity, source of controls, cancer types, and genotype methods.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the inclusion criteria, 8 case-control studies (Kuwai et al, 2004;Ling et al, 2005;Fransen et al, 2006;Li et al, 2009;Hsiao et al, 2010;Knechtel et al, 2010;Kang et al, 2011;Wang et al, 2011) were included in this meta-analysis and 91 articles were excluded. The flow chart of the study selection process is shown in Figure 1.…”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,14,15 İlginç olarak, böbrekte HIF-1alfa ve HIF-2alfa'nın her ikiside bulunmakta iken, miktarı fazla artan HIF-2alfa renal karsinoma hüc-relerinin çoğalmasına neden olur ve inhibisyonu bu çoğalmayı baskılamaya yeterlidir. 16 Bu nedenlerle, HIF-1alfa ve HIF-2alfa oldukça benzer olmalarına ve HIF-1alfa ile dimer oluşturarak hedef genlerin aynı DNA sekanslarına bağlanmalarına karşılık farklı doku ve hücresel yaygınlığa sahip olabilirler ve belkide farklı hedef genleri aktive edebilirler. HIF-1alfa ve HIF-2alfa gen mutasyonlarının her ikisinin de farelerde embriyonik öl-dürücü etki göstermeleri yanında farklı fonksiyonlara sahip oldukları gösterilmiştir.…”
Section: Introductionunclassified